The example of Christ and voluntary active euthanasia - Clark, W. Royce (Journal of religion and health, 1986)
The Christian church's aversion to suicide need not inform its position on voluntary active euthanasia any more than it informs its understanding of the role Jesus played in securing his own death. When the ontological polarity of freedom and destiny is kept in balance and is in agreement spontaneously and independently, culpability for the death of Jesus should be assigned neither to him nor to those who sought his crucifixion. This correspondence of freedom and destiny results in a theonomous moment, transcending all guilt. Similarly, when one elects to die because that choice best corresponds with one's self-image, it is extremely doubtful that this act of faith can be made intelligible or justified to others. If Jesus is example and not merely redeemer, this understanding implies that all people should be afforded the same freedom in death that jesus was without incurring moral guilt.